COVID-19 Shows the Need for a Global Animal Law - Anne Peters (Universitat Autonoma de Barcelona. Facultat de Dret, 2020)
The pandemic COVID-19 ─ which is a zoonosis ─ illustrates how problems of global nature and proportions stem from human use and abuse of animals and therefore underlines the necessity of a global law approach. The social, ecological, and economic consequences of animal exploitation, notably (but not limited to) agriculture, range from human poverty to transnational organised wildlife crime, to global warming, and of course to animal suffering. Not the least, the danger of the outsourcing of animal-processing industries and research facilities to animal cruelty havens and the threat of a regulatory chill on the national level suggest that the regulatory response to animal issues needs to be global. The Office International des Epizooties (OIE) could be transformed into the institutional hub for such an approach. The contribution also addresses and refutes the challenge of cultural and legal imperialism that is mounted against such a global law approach. It suggests to develop further the One Health paradigm for containing the pandemic and for combatting future zoonoses. The paper concludes that a critical global animal law approach will be helpful for overcoming the COVID-crisis and is generally warranted for transforming human─animal interaction.